Membangun Generasi Tangguh melalui Pendidikan Agama Islam Berbasis Kecerdasan Spiritual - Muhammad Rizal; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
In an era of globalization that is full of challenges and changes in values, building a resilient generation is an urgent need in the world of education. Islamic Religious Education has a strategic role in shaping the character and spirituality of students. This literature study aims to examine how the approach of Islamic Religious Education that integrates spiritual intelligence can shape a generation that is emotionally, socially, and morally resilient. This research method uses a qualitative approach with literature study as the main technique. Data sources come from national and international journals, scientific books, and relevant articles published in the last 10 years. The results of the study show that Islamic Religious Education based on spiritual intelligence can increase self-awareness, sense of responsibility, social sensitivity, resilience in facing life's tests, and the ability to make decisions based on divine values. By instilling spiritual values ​​such as sincerity, patience, gratitude, and tawakal, students can develop into individuals who are resilient and have high integrity. This study recommends that educators and educational institutions better integrate religious learning with applicable and contextual spiritual development. Thus, education not only shapes intellectual intelligence, but also strength of heart and personal integrity.